2023
DOI: 10.3390/v15071532
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Cannabis Virology: From the Virome Investigation to the Development of Viral Biotechnological Tools

Abstract: Cannabis sativa cultivation is experiencing a period of renewed interest due to the new opportunities for its use in different sectors including food, techno-industrial, construction, pharmaceutical and medical, cosmetics, and textiles. Moreover, its properties as a carbon sequestrator and soil improver make it suitable for sustainable agriculture and climate change mitigation strategies. The increase in cannabis cultivation is generating conditions for the spread of new pathogens. While cannabis fungal and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Therefore, while the diagnostic assays described in this study provide confirmation of pathogen presence, their causation or involvement in symptom expression remains to be confirmed. In previous experimental inoculations conducted on hemp plants by Keglar and Sparr [ 27 ] (summarized by Miotti et al [ 28 ]), it was reported that a number of mechanically transmitted viruses could cause mosaic and mottling symptoms on leaves, including AMV, CMV, potato viruses X and Y, and arabis mosaic virus. None of these viruses were identified in this study on cannabis, while AMV was detected in hemp plants in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, while the diagnostic assays described in this study provide confirmation of pathogen presence, their causation or involvement in symptom expression remains to be confirmed. In previous experimental inoculations conducted on hemp plants by Keglar and Sparr [ 27 ] (summarized by Miotti et al [ 28 ]), it was reported that a number of mechanically transmitted viruses could cause mosaic and mottling symptoms on leaves, including AMV, CMV, potato viruses X and Y, and arabis mosaic virus. None of these viruses were identified in this study on cannabis, while AMV was detected in hemp plants in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…BCTV exists as phylogenetically different strains and is reported to affect hemp grown in Colorado, Arizona, Nevada, Oregon, Washington, and California [ 3 , 34 , 35 , 36 , 37 , 39 , 41 ]. The virus has an extremely wide host range and is considered to be a pathogen that poses a significant threat to this crop [ 28 ]. Additional research is likely to identify more viruses and phytoplasmas occurring on both cannabis and hemp, particularly where these crops are grown in close proximity to nonhemp crops that can provide a source of inoculum for spread to cannabis and hemp plants, in addition to the presence of insect vectors that can transmit these pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations